2011
DOI: 10.1371/journal.pone.0026931
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Recognizing Mycobacterium avium paratuberculosis Epitopes Cross-React with the Beta-Cell Antigen ZnT8 in Sardinian Type 1 Diabetic Patients

Abstract: The environmental factors at play in the pathogenesis of type 1 diabetes (T1D) remain enigmatic. Mycobacterium avium subspecies paratuberculosis (MAP) is transmitted from dairy herds to humans through food contamination. MAP causes an asymptomatic infection that is highly prevalent in Sardinian T1D patients compared with type 2 diabetes (T2D) and healthy controls. Moreover, MAP elicits humoral responses against several mycobacterial proteins. We asked whether antibodies (Abs) against one of these proteins, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 46 publications
(66 reference statements)
5
74
0
Order By: Relevance
“…This similarity may cause autoimmunity by molecular mimicry between MAP antigens and pancreatic islet β-cells, and trigger islet cell depletion. These results are in line with previous studies performed in Sardinia [19,26].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This similarity may cause autoimmunity by molecular mimicry between MAP antigens and pancreatic islet β-cells, and trigger islet cell depletion. These results are in line with previous studies performed in Sardinia [19,26].…”
Section: Discussionsupporting
confidence: 93%
“…The association of MAP with T1DM has been reported in Sardinia, known to have a high prevalence of type 1 diabetes and a high rate of MAP infection among sheep and cattle [6][7][8]19,27]. However, Rani et al could not find any association despite the high prevalence of MAP and T1DM in India, probably due to the low number of patients investigated [21] or the genetic predisposition of the infected population in developing such an autoimmunity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…paratuberculosis represents a major threat to dairy cattle (4,6) with the potential to spread to humans (39)(40)(41)(42)(43). Earlier reports indicated that M. avium subsp.…”
Section: Discussionmentioning
confidence: 99%